Data Encryption Based Blockchain and IoT (Eurasian Journal of Engineering and Technology, 2022)
Over the decades, several studies have been conducted on the art of cryptography which is the process of transforming secret data into an unreadable or scrambled form. More specifically, it is a technique to achieve the message secretly. however, the techniques that achieve the cipher data depending on many algorithms which make data unreadable to the human eye unless decrypted by the same algorithm that is predefined by the sender. Thus, in assessing the legitimacy of a traded information, hubs should arrive at an agreement to play out an uncommon activity, where case the chance to enter and record exchanges and problematic cooperation with the framework is fundamentally decreased. As of late, to share and access the executives of IoT devices data with disseminated demeanor another confirmation convention dependent on block-chain is proposed and it is guaranteed that this convention fulfills client protection, saving and security